These tangled threads : a novel of Biltmore [large type] - Thomas, Sarah Loudin (Thorndike Press large print Christian fiction, 2024)
"Seven years ago, a hidden betrayal scattered three young friends living in the shadow of the great Vanderbilt mansion. Now, when Biltmore Industries master weaver Lorna Blankenship is commissioned to create an original design for Cornelia Vanderbilt's 1924 wedding, she panics knowing she doesn't have the creativity needed. But there's an elusive artisan in the Blue Ridge Mountains who could save her--if only she knew where to begin.To track down the mysterious weaver, Lorna sees no other way than to seek out the relationships she abandoned in shame. As she pulls at each tangled thread from her past, Lorna is forced to confront the wounds and regrets of life long ago. She'll have to risk the job that shapes her identity, as well as the hope of friendship--and love--restored"--